2023
DOI: 10.1186/s13722-023-00398-7
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative interview study of patient experiences of receiving motivational enhancement therapy in a Swedish addiction specialist treatment setting

Stina Ingesson Hammarberg,
Jennie Sundbye,
Rebecca Tingvall
et al.

Abstract: Background Motivational enhancement therapy (MET) has shown to be efficacious as treatment of alcohol use disorder (AUD), in reducing alcohol consumption and related consequences. However, qualitative research on how patients perceive this treatment is lacking. The aim of this study was to explore how patients experience MET as a treatment for AUD. Methods Fifteen patients (8/7 female/male) participated in semi-structured interviews after receiving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The MET manual does not include any specific guidance on how to reach goals to reduce drinking or how to abstain from alcohol, which may be less favorable when aiming for a CD goal as opposed to abstinence. In a qualitative interview study from the current trial on patients’ experiences from receiving MET, the results indicated that some of the patients found the treatment to lack specific guidance on how to attain a CD goal [ 78 ]. These results taken together indicate that the MET manual may need modification to also suit both abstinent- and CD treatment goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MET manual does not include any specific guidance on how to reach goals to reduce drinking or how to abstain from alcohol, which may be less favorable when aiming for a CD goal as opposed to abstinence. In a qualitative interview study from the current trial on patients’ experiences from receiving MET, the results indicated that some of the patients found the treatment to lack specific guidance on how to attain a CD goal [ 78 ]. These results taken together indicate that the MET manual may need modification to also suit both abstinent- and CD treatment goals.…”
Section: Discussionmentioning
confidence: 99%
“…However, the actual number of treatment sessions delivered was not different between groups, as an extra session was more commonly added in the MET condition, compared to in the BSCT arm. The aforementioned qualitative study on patient experiences on receiving MET as their treatment demonstrated that the treatment was perceived as too brief [ 78 ]. This may have affected the therapists’ decision to add an extra session to comparably more patients in the MET group, than what was the case in BSCT.…”
Section: Discussionmentioning
confidence: 99%